Knockdown of circular RNA VANGL1 inhibits TGF‐β‐induced epithelial‐mesenchymal transition in melanoma cells by sponging miR‐150‐5p. Issue 23 (9th November 2021) - Zhou, Hongfeng; Wu, Jin; Leng, Shaolong; Hou, Chongchao; Mo, Laiming; Xie, Xue; Wang, Ling; Xu, Yunsheng
Abstract: Melanoma is one of the most aggressive and life‐threatening skin cancers, and in this research, we aimed to explore the functional role of circular RNA VANGL1 (circVANGL1) in melanoma progression. The expression levels of circVANGL1 were observed to be significantly increased in clinical melanoma tissues and cell lines. Moreover, circVANGL1 knockdown suppressed, while circVANGL1 overexpression promoted the proliferation, migration and invasion abilities of melanoma cells. Further investigations confirmed the direct binding relation between circVANGL1 and miR‐150‐5p in melanoma, and restoration of miR‐150‐5p blocked the effects of circVANGL1 overexpression in melanoma cells. We further found that circVANGL1 was up‐regulated by TGF‐β treatment, and the enhanced EMT of TGF‐β‐treated melanoma cells was blocked by circVANGL1 knockdown. In conclusion, these results indicated that circVANGL1 might serve as a promising therapeutic target for melanoma.